Analysis Of Krosok Salt Compound Content From The Results Of The Salt Farmers Group In Kersik Village Kutai Kartanegara Regency - Barolym Tri Pamungkas (International Journal of Medicine and Health, 2024)
Salt is a source of electrolytes and iodine which are very important for the human body. East Kalimantan Province has the potential for diverse coastal and marine resources with high economic value, so it has great potential for optimal, effective, efficient and sustainable management. This research aims to determine the compound content of krosok salt that will be distributed to the public with NSI. This research method is based on NSI 3556:2016 and Atomic Absorption Spectrophotometry (AAS) method, including: (1) Water content analysis; (2) Analysis of the part that is not soluble in water; (3) NaCl content; (4) KIO3 levels; (5) Analysis of metal contamination. This research was conducted on krosok salt in Kersik Village, Kutai Kartanegara Regency. The NaCl salt content does not meet the minimum NSI requirements, namely 94%. Meanwhile, Pb, Cd, metal contamination meets the requirements with values ​​below 10 mg/kg and 0.5 mg/kg.